Lab of Things: A Platform for Conducting Studies with Connected Devices in Multiple Homes - Brush, A.J.; Filippov, Evgeni; Huang, Danny; Jung, Jaeyeon; Mahajan, Ratul; Martinez, Frank; Mazhar, Khurshed; Phanishayee, Amar; Samuel, Arjmand; Scott, James; Singh, Rayman Preet (ACM UbiComp'13 Adjunct, 2013)
Researchers who develop new home technologies using connected devices often want to conduct large-scale field studies in homes to evaluate their technology, but conducting such studies today is extremely challenging. Inspired by the success of PlanetLab, which enabled development and evaluation of global network services, we are developing a shared infrastructure for home environments, called Lab of Things. Our goal is to substantially lower the barrier to developing and evaluating new technologies for the home environment.